Factors determining spontaneous ventricular defibrillation - Tribulova, Narcis (Pulsus Group Inc, 2001)
Ventricular fibrillation (VF) is defined as a sustained, fatal reentrant arrhythmia that never terminates spontaneously and requires artificial electrical defibrillation. For many years it was believed that spontaneous ventricular defibrillation (SVD) appears only in hearts with small muscle mass that cannot continue fibrillating. SVD appears even in humans, and some drugs transform sustained VF into a transient VF, reverting spontaneously into sinus rhythm. The present criteria for VF were based on the wavelength theory. Accordingly, the persistence of fibrillation depends on the wavelength of the reentrant impulse. Fibrillation can be sustained only if the reentrant circuit is smaller than the length of the refractory tissue. Following this assumption, lengthening of action potential duration (APD) and effective refractory period (ERP) were accepted as factors that determine antiarrhythmic defibrillating ability. The results of recent studies questioned this postulation and clearly showed that prolongation of APD is proarrhythmic. In examining the differences between transient and sustained VF in various mammals, it was hypothesized that SVD requires a high degree of myocardial gap junctional coupling and synchronization. Thus, any compound or condition that enhances intercellular coupling and synchronization or attenuates the dispersion of refractoriness can facilitate SVD. Because one of the main factors involved in intercellular uncoupling is an excess concentration of cytoplasmic free Ca(2+), it seems plausible that a compound that protects against Ca(2+) overload and has a positive inotropic effect can serve as a potent defibrillating agent. Evaluation of the anti-arrhythmic properties of various defibrillating compounds showed that a defibrillating drug has the ability to prevent or to attenuate Ca(2+) overload. By decreasing increased diastolic Ca(2+) concentration, they enhance intercellular coupling and synchronization, and consequently facilitate SVD, while prolongation of APD or ERP facilitates the appearance of arrhythmias and VF. The novel approach based on upregulation of intercellular coupling to enhance synchronization and on decreased dispersion of refractoriness without prolongation of APD should be taken into consideration in future development of new potent cardioprotective-defibrillating drugs.